NEUROPSYCHOLINGUISTIC ANALYSIS OF THE CONCEPTS "ANGER AND HATE" - Bobokalonov Ramazon Rajabovich; O’ktamov Hasan G’olib o’g’li (Bright Mind Publishing, 2025)
This article presents a scientific discussion of the controversial conceptual features, neurological, psychological, and linguistic factors of the concepts of anger and hatred. Theoretical ideas on this topic are presented within the framework of the requirements of the modern field of neuropsycholinguistics. In this article, the author addresses a pressing issue: translating neuropsycholinguistics from denominator to image — applying theory to practice across a broad range, scientifically explaining the influence of anger and hatredon the human psyche, health, and physical activity.